Freud como lector de Nietzsche. La influencia de Nietzsche en la obra de Freud. (2015)
This article aims to contribute to the understanding of the nature of the influence of Nietzsche’s thought in the work of Freud. To meet this objective a thorough analysis of the texts of Nietzsche and Freud is done, the respective biographies are examined and the specialized bibliography about the links between the two authors is reviewed. Based on the evidence gathered, we conclude with a reflection that deals with the complex relationship of Freud to Nietzsche from the concept of the abominable, which is key to understand the history and drift of Freudian thought.